Analisis Kandungan Nitrogen (N) dan Posforus (P) pada Limbah Jeroan Ikan Mujair (Oreochromis mosambicus) Danau Lindu - Hildawianti, Hildawianti; Tiwow, Vanny M. A.; Abram, Paulus Hengky (Jurnal Akademika Kimia, 2017)
An effort to minimize the environmental pollution is using that waste as a base material of organic fertilizer. This study was conducted to determine the levels of Nitrogen (N) and phosphorous (P) contained in the offal waste of mujair fish (Oreochromis mosambicus) from Lindu lake. Samples of mujair offal waste were taken from fish saler on the street Towua, Palu. Analysis of Nitrogen levels usedKjeldhal method which consists of three phases, namely destruction, distillation, and titration. On the other hand, for Phosphorus analysis was using wet digestion method, followed by absorbance measurements of samples with spectronic 20 at a wavelength of 720 nm. Based on the analysis, the average of nitrogen (N) levels in mujair offal waste was 2.78%, while the average of phosphorus (P) levels was 2.48%. From these results, it is known that mujair offal waste contains more nitrogen (N) compared to phosphorous (P). In addition, when compared to the quality standard liquid organic fertilizer N and P content in mujair offal almost meets the quality standard liquid fertilizer, where the minimum technical requirements of organic liquid fertilizer should contain a total N content of 3-6% and 3-6% P2O5.